Ember risk modelling for improved wildfire risk management in the peri-urban fringes. (April 2021) - Roberts, Melanie E.; Rawlinson, Andrew A.; Wang, Ziyuan
Abstract: Although embers are a leading cause of house loss and damage from wildfire, risk reduction activities such as vegetation management and planning requirements do not adequately account for the risk of embers. To help address this, a model of the potential ember risk is presented. It takes into account local vegetation and background wind conditions for both long-range and short-range ember dispersal. This model is developed to provide indications of the importance of embers to the household-level wildfire risk in communities at the wildland-urban interface. The model provides information for householders to improve understanding of the nature of ember risk within the community, and to assist planning in order to respond to that risk. A case study of the 2015 Warringine Park (Coastal Section) bushfire in Australia is presented, which demonstrates how the model could be used to assist with community planning. The utility of this outcome for community and household level wildfire planning and preparation is discussed. Graphical abstract: Image 1 Highlights: Developed new household level model for risk posed by embers. Scalable model with minimal data requirements. Application of the model demonstrated for the 2015 Warringine Park bushfire, Victoria, Australia.